The Dark World of Women Victims of Violence: A Qualitative Analysis of Police Reports - Souza, Aline Pereira de; Marin, Maria José Sanches; Rodrigues, Paula Sales [UNESP] (Ludomedia Unipessoal Lda, 2021)
This article aims to identify, verify and examine the documents of the Women's Police Station (DDM) of the Judicial Police of Marilia city in the perspective of a cross-sectional study in the quantitative modality using the thematic analysis technique, carried out based on police reports of violence against women (BO), in order to reveal the magnitude of violence through a qualitative approach, contributing to the advancement in the understanding of this complex phenomenon that lacks effective health interventions. The analysis portrayed women vulnerability factors and relationships of inequality across their attackers, as well as the coercive behaviors and control. Death threats occur under different conditions and forms, physical assaults are degrading, and verbal assaults, moral damage, intimidation, persecution and injuries are also evident. Violence that generates insecurity and fear in women who seek in the police report a right that should be irrevocable life. It is understood that it is essential to articulate preventive intersectorial actions and promotion of health in order to break the violence cycle.
O Mundo Sombrio das Mulheres Vítimas de Violência: Uma Análise Qualitativa dos Boletins de Ocorrência
Keywords: Domestic violence; Family Relationships; Women